Mechanisms and clinical progress of adipose-derived stem cells and their derivatives in the treatment of hair loss - Jiale Zhang; Feng Chen; Yue Hu; Xianling Cong (Stem Cell Research & Therapy)
Abstract The rising prevalence of alopecia poses a significant challenge for both clinicians and researchers. As the global incidence of hair loss continues to increase, research into hair biology and regenerative mechanisms has gained considerable attention. However, current treatment options for alopecia are often constrained by limited efficacy and notable adverse effects. This underscores an urgent need for innovative therapeutic strategies to address these gaps. Adipose-derived stem cells (ADSCs), a subset of mesenchymal stem cells, represent a promising new approach in the treatment of alopecia. This review provides a detailed examination of the fundamental properties of ADSCs and their derivatives, exploring their mechanisms of action in alopecia therapy. Analysis of the efficacy of ADSCs and their derivatives in both preclinical and clinical settings highlight their potential to stimulate hair regeneration. Additionally, the review discusses various pre-treatment methods designed to enhance the regenerative capacity of ADSCs in hair growth, elucidating the mechanisms involved. The review also addresses the challenges and future directions for the use of ADSCs in alopecia treatment, aiming to offer valuable insights for both theoretical research and clinical practice. Ultimately, this work seeks to contribute to the development of more effective treatment regimens for alopecia.